Upaya Perlindungan Hukum Hak Privasi Terhadap Data Pribadi Dari Kejahatan Peretasan - Agustina, Winda; Wiraguna, Sidi Ahyar (Media Hukum Indonesia (MHI), 2025)
This study aims to analyze the form of legal protection of the right to privacy of personal data in the face of hacking crimes according to Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The research method used is normative juridical with a statutory approach. The results show that the PDP Law provides a strong legal basis for the protection of personal data, including data subject rights mechanisms, data controller obligations, and administrative and criminal sanctions for violations. However, the implementation of this law still faces challenges, such as weak cyber law enforcement infrastructure and limited public digital literacy. Therefore, it is necessary to strengthen the institutionalization of supervisory authorities, increase the capacity of law enforcement officers, and educate the public to support the effectiveness of legal protection of personal data from hacking crimes.